Pecak Lele Cooking Training as a New Culinary MSME in Bekelir Babakan Village, Tangerang - Antony Stefanus Purba; Iwan Setiawan (Jurnal Pengabdian Masyarakat Bestari, 2023)
This community service is useful for helping residents of Kampung Bekelir who want to have additional income through a culinary business which is also an attraction in Tangerang City as well as in Kampung Bekelir which already has several culinary establishments that are already operating. This pecak lele training teaches the community in the process of making and can try it directly so as to produce a typical pecak lele creation that is different from the existing pecak lele. Counseling on how to make standard menus so as to help the community in making the pecak lele culinary business in Bekelir village. The community will also make healthy catfish halibut according to current trends with the addition of ginger and pure coconut milk in the manufacture.